Predictors of a Rapid Decline of Renal Function in Patients with Chronic Kidney Disease Referred to a Nephrology Outpatient Clinic: A Longitudinal Study. (8th December 2015) - Vigil, Ana; Condés, Emilia; Camacho, Rosa; Cobo, Gabriela; Gallar, Paloma; Oliet, Aniana; Rodriguez, Isabel; Ortega, Olimpia; Mon, Carmen; Ortiz, Milagros; Herrero, Juan Carlos
Abstract : Background. Predicting the progression of kidney failure in patients with chronic kidney disease is difficult. The aim of this study was to assess the predictors of rapid kidney decline in a cohort of patients referred to a single outpatient nephrology clinic. Design. Longitudinal, prospective cohort study with a median follow-up of 3.39 years. Methods. Data were obtained from 306 patients with chronic renal failure based on serum creatinine-estimated glomerular filtration rate (e G F R c r e a t ) < 90 mL/min/1.73 m 2 . After excluding patients who died (n = 30 ) and those who developed end-stage renal failure (n = 6 ), 270 patients were included. This population was grouped according to the rate of kidney function decline. Rapid kidney function decline was defined as an annuale G F R c r e a t loss > 4 mL/min/1.73 m 2 . We recorded nonfatal cardiovascular events at baseline and during follow-up in addition to biochemical parameters. Results. The mean loss in renal function was 1.22 mL/min/1.73 m 2 per year. The mean age was 75 ± 8.8 years old, and the mean baselinee G F R c r e a t was 42 ± 14 mL/min/1.73 m 2 . Almost one-fourth of the sample (23.3% [63 patients]) suffered a rapid decline in renal function. In a logistic regression model with rapid decline as the outcome, baseline characteristics, lower serum albumin (OR: 0.313, 95% CI: 0.114–0.859), previous cardiovascular disease (OR: 1.903 95% CI: 1.028–3.523), and higher proteinuria (g/24 h) (OR: 1.817 CI 95%: 1.213–2.723) were the main predictors of rapid kidney decline. On multivariate analysis, including baseline and follow-up data, we obtained similar adjusted associations of rapid kidney decline with baseline serum albumin and proteinuria. The follow-up time was also shorter in the group with rapid rates of decline in renal function. Conclusion. Renal function remained stable in the majority of our population. Previous cardiovascular disease and cardiovascular incidents, lower serum albumin, and higher proteinuria at baseline were the main predictors of rapid kidney decline in our population.